163k views
2 votes
The system of linear equations 5x+3y=3 and x+y=-1 is graphed below. What is the solution to the system of equations?

1 Answer

4 votes

Answer:

x=3. y =-4

Explanation:

For the given system, we need to merge the equations, and obtain the first variable.

So, the second (x+y= -1) multiply it by -3 and sum it to the first one

5x+3y=3. By doing this, you have the following>

2x=6, thus we obtain that x =3

Knowing that x=3, we can obtain the value for 'y' variable, you must use the other equation, (x+y=-1), from where we obtain that y=-4

User Svanryckeghem
by
4.9k points